Navigating challenges: a case report on complications in clavicle fracture management with ’K’ wire fixation - Prasath, G. Lakshman (International Journal of Research in Orthopaedics, 2023)
Orthopaedic metallic pins and wires are commonly used for the fixation of fractures and dislocations, with the shoulder girdle being one of the common areas for their application. Despite recent precautionary measures, complications related to migration of these devices into the pleural cavity continue to be reported. We present a case of a Kirschner wire (K-wire) migration from a left clavicle fracture to the first rib, highlighting the importance of vigilance and immediate intervention in such cases. A 35-year-old female, previously operated for a left clavicle fracture using K-wire and tension band wiring, presented with left shoulder and chest pain eight years later. Radiological investigations revealed a broken K-wire in the pleural cavity, with one portion near the acromio-clavicular region and the other at the posterior aspect of the first rib. Surgical intervention was performed, involving the removal of the K-wire from the chest cavity and clavicle, with subsequent patient recovery. The migration of orthopaedic pins and wires into the chest cavity is a rare but well-documented complication. Previous reports have demonstrated severe consequences, including cardiovascular complications and fatalities. Theories explaining wire migration include muscle action, shoulder mobility, negative intrathoracic pressure during respiration, regional bone resorption, gravitational forces, and even capillary action. To minimize such complications, subcutaneous K-wire ends should be bent, and restraining devices should be used. Close clinical and radiographic follow-up is essential until the pins and wires are removed after achieving the therapeutic goal. In case of migration, prompt removal is necessary to prevent fatal complications. This case report emphasizes the significance of vigilance and proper precautions when using orthopaedic pins and wires for shoulder girdle fractures. Timely intervention is crucial to mitigate severe complications associated with migration. Sharing experiences and lessons learned can contribute to the safer application of these fixation devices in orthopaedic practice.